The Institutional Context of an 'Empirical Law': The Wage Curve under Different Regimes of Collective Bargaining - Blien, Uwe; Dauth, Wolfgang; Schank, Thorsten; Schnabel, Claus (British Journal of Industrial Relations, 2013)
The wage curve postulates that the wage level is a decreasing function of the regional unemployment rate. In testing this hypothesis, most studies have not taken into account that differences in the institutional framework may have an impact on the existence (or the slope) of a wage curve. Using a large-scale linked employer-employee dataset for Western Germany, this article provides a first direct test of the relevance of different bargaining regimes (and of works councils) for the existence of a wage curve. In pooled regressions for the period 1998 to 2006, as well as in worker-level or plant-level fixed-effects estimations, we obtain evidence for a wage curve for plants with a collective bargaining agreement at firm level. The point estimates for this group of plants are close to the -0.1 elasticity of wages with respect to unemployment postulated by Blanchflower and Oswald. In this regime, we also find that works councils dampen the adjustment of wages to the regional unemployment situation. In the other regimes of plants that either do not make use of collective contracts or apply sectoral agreements, we do not find a wage curve. © 2011 Blackwell Publishing Ltd/London School of Economic
WiSo-Import:2015-03-26:4084
Keywords: wages; wage curve; collective bargaining; Germany